2013
DOI: 10.1038/cddis.2013.31
|View full text |Cite
|
Sign up to set email alerts
|

Myostatin induces mitochondrial metabolic alteration and typical apoptosis in cancer cells

Abstract: Myostatin, a member of the transforming growth factor-β superfamily, regulates the glucose metabolism of muscle cells, while dysregulated myostatin activity is associated with a number of metabolic disorders, including muscle cachexia, obesity and type II diabetes. We observed that myostatin induced significant mitochondrial metabolic alterations and prolonged exposure of myostatin induced mitochondria-dependent apoptosis in cancer cells addicted to glycolysis. To address the underlying mechanism, we found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 53 publications
3
35
1
Order By: Relevance
“…A functional role for MSTN in regulating myogenic development was further supported by the phenotypes associated with naturally occurring mutations of the MSTN gene in cattle and humans [2,3]. Recent studies have demonstrated non-muscle functions of MSTN in the regulation of adipogenesis [4,5], cardiac myocyte hypertrophy [6] and glucose metabolism [7], and cancer cell apoptosis [8]. Given the profound biological significance of MSTN, there is considerable interest in identifying the molecular mechanisms underlying MSTN-regulated cellular responses.…”
Section: Introductionmentioning
confidence: 98%
“…A functional role for MSTN in regulating myogenic development was further supported by the phenotypes associated with naturally occurring mutations of the MSTN gene in cattle and humans [2,3]. Recent studies have demonstrated non-muscle functions of MSTN in the regulation of adipogenesis [4,5], cardiac myocyte hypertrophy [6] and glucose metabolism [7], and cancer cell apoptosis [8]. Given the profound biological significance of MSTN, there is considerable interest in identifying the molecular mechanisms underlying MSTN-regulated cellular responses.…”
Section: Introductionmentioning
confidence: 98%
“…Release of cytochrome c can induce non-specific autophagy within the cell. Several different mechanisms can trigger the release of cytochrome c: CL peroxidation, leakage through the mitochondrial permeability transition (MPT) pore complex, Bax and Bak interactions with voltage-dependent anion channel (VDAC), and high K + level in extra-mitochondrial matrix (Gogvadze et al, 2006; Liu et al, 2013; Tan et al, 2005). …”
Section: Introductionmentioning
confidence: 99%
“…Western blotting was performed accordingly to the methods described previously [21]. Cells or nuclear fractions were lysed in lysis buffer (10 mM HEPES, pH 7.4, 2 mM EGTA, 0.5% NP-40, protease inhibitors).…”
Section: Sds-page and Immunoblottingmentioning
confidence: 99%